The Learning Concept of Pondok Songserm Islam Wittaya, Takamcham Sub-district, Nong Chik Regency, Pattani, Southern Thailand - Putro, Trias Setyo (Jurnal Pendidikan Islam, 2017)
Pondok Pesantren is a kind of Islamic boarding school that often to be heard in Indonesia and one of the uniqueness of Islamic education in the world. Nevertheless, the researcher found another fact when the researcher got a teaching practice abroad for six months. The researcher found the existence of Pondok pesantren in Thailand. Generally, Thailand is a Buddhist majority except for several provinces in Southern Thailand, which border to Malaysia. They are Narathiwat, Pattani, Yala, Nakhon Sri Thammarat, and a part of Songkhla. Those provinces are majority Muslims. Considering the fact above, it could not be ignored by the educational concept that offered to the young generation in those areas largely have a basic of Islam. The main question will appear to know more about the Islamic education system, especially about the Pondok Pesantren in overseas. In this case, the object of the research is determined in Pondok Songserm Islam Wittaya, Takamcham Sub-district, Nong Chik Regency, Pattani province, Southern Thailand.